Hubungan Tingkat Pendidikan Formal Akseptor KB Aktif Dengan Kemandirian KB Di Kecamatan Sukoharjo Kabupaten Sukoharjo - Mustafa Mahmud Al Jufri; Endang Sutisna; AA Subijanto (Nexus Kedokteran Komunitas, 2013)
Background : The level of formal education an active family planning acceptors are factors that may influence the attitudes and behavior of people to use an independence KB. By knowing the factors that affect a person's use of family planning will be able to improve the coverage of family planning more widely. This study aimed to determine whether there is a relationship between the level of formal education with self-reliance active family planning acceptors of family planning in Subdistrict Sukoharjo District Sukoharjo. Methods : This study is observational with case control conducted in October-November 2012 on 100 samples of family planning acceptors active in Subdistrict Sukoharjo District Sukoharjo. Sampling technique in this study using current Simple Random Sampling. Taking data from the sample using a questionnaire containing variable levels of education and independence KB. Data analysis using odd ratio with univariate and bivariate analyzes. Results : Statistical test result value of odd ratio test are OR = 10,120, 95% CI = 3,062 33,450, p = 0,000. Value of p <0.05 means that the significance level of 5% or 95% level of confidence is significant relationship between the two variables. Conclusion : From this study it was concluded that the higher levels of formal education an active family planning acceptors, the greater the tendency to carry out family planning independently. Key words : Independence KB, formal education, active KB acceptor